Development of STEM-Based Physics Module with Self-Regulated Learning to Train Students Critical Thinking Skills - Heryani, Tiastuti Putri; Suwarma, Irma Rahma; Chandra, Didi Teguh (Postgraduate, University of Mataram, 2023)
One of the 21st century skills is critical thinking skills. However, according to several research results, it shows that students’ critical thinking skills in Indonesia are still low. This is caused by inappropriate learning process, so that it has an impact on the effectiveness of achieving competence in learning. Teaching materials are one of the most important parts that support the learning process. A module is a form of teaching material that is structured to help students master learning objectives. Modules to practice critical thinking skills according to 21st century skills, which are integrated with the STEM approach. Therefore, this study aims to develop a STEM-based physics module with self-regulated learning to train students critical thinking skills. The SRL agent will assist students in studying the material in the module. The method used is a mixed method, with an exploratory sequential design. Mixed method is a combination of qualitative and quantitative research methods in a study. Qualitative data is needed in designing physics modules, while quantitative data is needed to determine the validity of the modules feasibility in practicing critical thinking skills. The critical thinking skills instrument was developed based on aspects of critical thinking skills according to Ennis. Data collection comes from expert validation result sheets. The results of this development indicate that STEM-based modules with SRL agents are feasible to use properly. And during the learning process is expected to improve students critical thinking skills. Therefore, students critical thinking skills still need to be studied in learning.